Developing a questionnaire to assess the health effects of bioaerosols. (30th June 2018) - Basu, S; Poole, J; Frost, G; Fox, D
Abstract: Background: Bioaerosol exposure occurs in several industries including green waste recycling, poultry farming, grain, animal feed and cotton production. Whilst several studies have investigated exposure and health effects in compost workers, the best questions to ask about health are uncertain. Aims: This study aimed to develop a questionnaire to assess health symptoms in compost workers. Methods: A 46-item questionnaire to ascertain possible symptoms of occupational illness related to bioaerosol exposure in a cohort of UK industrial compost workers and delivery in an interviewer-led format. The reliability of the questionnaire was assessed using Cronbach's α. A principal component analysis (PCA) was conducted to condense the questionnaire for practical purposes. Results: One hundred and eleven (89%) workers completed the questionnaire. All items showed very good reliability (Cronbach's α = 0.83). After removing perfectly correlated questions from the data set, the PCA was conducted on a reduced data set of 28 items to explore underlying themes. Nine components were identified that explained 77% of the total variation. Nine of the questions removed prior to PCA due to perfect correlation were reintroduced because they added clinical value. The final questionnaire therefore consisted of 37 items and retained very adequate reliability (Cronbach's α = 0.76). Conclusions: Our health questionnaire has demonstrated adequate reliability when used within this industrial composting workforce. Further applications may include health surveillance, investigating outbreaks of occupational disease or research. Future work should examine the predictive validity of the questionnaire in these settings.